Ilegal : reflexiones de un inmigrante indocumentado - Navejas, José Ángel (Latinos in Chicago and the Midwest., 2019)
"A day after N. first crossed the U.S. border from Mexico, he was caught and then released onto the streets of Tijuana. Undeterred, N. crawled back through a tunnel to San Diego, where he entered the United States forever. Illegal: Reflections of an Undocumented Immigrant is his timely and compelling memoir of building a new life in America. Authorial anonymity is required to protect this life. Arriving in the 1990s with a 9th grade education, N. traveled to Chicago where he found access to ESL classes and GED classes. He eventually attended college and graduate school and became a professional translator. Despite having a well-paying job, N. was isolated by a lack of official legal documentation. Travel concerns made big promotions out of reach. Vacation time was spent hiding at home, pretending that he was on a long-planned trip. The simple act of purchasing his girlfriend a beer at a Cubs baseball game caused embarrassment and shame when N. couldn't produce a valid ID. A frustrating contradiction, N. lived in a luxury high-rise condo but couldn't fully live the American dream. He did, however, find solace in the one gift America gave him--his education. Ultimately, N.'s is the story of the triumph of education over adversity. In Illegal he debunks the stereotype that undocumented immigrants are freeloaders without access to education or opportunity for advancement. With bravery and honesty, N. details the constraints, deceptions, and humiliations that characterize alien life "amid the shadows.""--